2018
DOI: 10.18805/ijare.a-4702
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for estimation of reference evapotranspiration in North-Central Plateau zone of Odisha

Abstract: Estimation of Evapotranspiration is vital role for proper water management and efficient farming activities. A decision support system (DSS_ET) was developed which supports 22 ET0 estimation methods with varied options for calculation of various intermediate parameters. The objective of the study is to estimate ET0 in the North central Plateau zone of Odisha, using weather data of the respective locality and screening of methods to estimate ET0 close to FAO-56 Penman Monteith method. The FAO-24 Penman(c=1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Djaman et al (2013) reported that ET r values ranged from 0.4 to 12.3 mm d −1 . Other studies have shown ET r values of 2.54–10.32 mm d −1 (Khatua & Pasupalak, 2018), 3.01–5.59 mm d −1 using 16 different mathematical models (Liu et al, 2017) and 1.1–8.0 mm d −1 (Upadhyaya, 2016). There were some differences in seasonal ET values in the different studies.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Djaman et al (2013) reported that ET r values ranged from 0.4 to 12.3 mm d −1 . Other studies have shown ET r values of 2.54–10.32 mm d −1 (Khatua & Pasupalak, 2018), 3.01–5.59 mm d −1 using 16 different mathematical models (Liu et al, 2017) and 1.1–8.0 mm d −1 (Upadhyaya, 2016). There were some differences in seasonal ET values in the different studies.…”
Section: Resultsmentioning
confidence: 95%
“…However, the accuracy of the reference equations varies widely under different climatic conditions. While some equations result in appropriate ET in specific climatic conditions, some give good results in all climatic conditions (Kashyap & Panda, 2001; Irmak et al, 2003b; Temesgen et al, 2005; Gavilán et al, 2008; Cao et al, 2014; Kar et al, 2017; Liu et al, 2017; Khatua & Pasupalak, 2018). Thus, different and/or the same equations tested sometimes resulted in different results under similar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of SM is lost through evapotranspiration process (Krishna, 2019). ETo indicates the environmental requirement for evaporation influenced by climatic factors (Katua and Pasupalak, 2018). Meanwhile, ETa shows crop water requirements controlled by climatic and plant factors (Prijono, 2009).…”
Section: Moisture Balance In the Coffee Root Zonementioning
confidence: 99%